Diversity of Rhizophydiales (Chytridiomycota) in Thailand: unveiling the hidden gems of the Kingdom - Vedprakash G. Hurdeal; Joyce E. Longcore; E. B. Gareth Jones; Kevin D. Hyde; Eleni Gentekaki (IMA Fungus)
Abstract Chytrids, often overshadowed by their other fungal counterparts, take center stage as we unravel the mysteries surrounding new species within Rhizophydiales and explore their unique characteristics. In the broader spectrum of chytrids, their significance lies not only in their roles as decomposers but also as key players in nutrient cycling within aquatic ecosystems as parasites and saprobes. Baited soil and aquatic samples collected from various provinces of Thailand, yielded new species of the Rhizophydiales (Chytridiomycota), some of which expanded previously single species genera. Our investigation incorporated a combination of morphological and phylogenetic approaches, enabling us to identify these isolates as distinct taxa. The novel isolates possess distinguishing features, such as variations in size and shape of the sporangium and zoospores, that somewhat differentiate them from described taxa. To confirm the novelty of the species, we employed robust phylogenetic analyses using maximum likelihood and bayesian methods. The results provided strong support for the presence of eight distinct lineages within the Rhizophydiales, representing our newly discovered species. Furthermore, we employed Poisson Tree Processes to infer putative species boundaries and supplement evidence for the establishment of our new Rhizophydiales species. By meticulously exploring their morphological characteristics and genetic makeup, we expand the known catalogue of fungal diversity by describing Alphamyces thailandicus, Angulomyces ubonensis, Gorgonomyces aquaticus, G. chiangraiensis, G. limnicus, Pateramyces pingflumenensis, Terramyces aquatica, and T. flumenensis and also provide valuable insights into the intricacies of this order. This newfound knowledge not only enriches our understanding of Rhizophydiales but also contributes significantly to the broader field of mycology, addressing a critical gap in the documentation of fungal species. The identification and characterization of these eight novel species mark a noteworthy stride towards a more comprehensive comprehension of fungal ecosystems and their vital role.